The Role of E-Commerce in Improving Incomes, Product Sales, and Market Reach of Culinary MSMEs in Pancoran Mas District of Depok City - Afiyah, Zakiyatul; Rachmawati, Rini; Kurniawan, Andri (Lembaga Dakwah dan Pembangunan Masyarakat Universitas Cokroaminoto Yogyakarta (LDPM UCY), 2025)
The smart economy is part of the smart city aspect that aims to support economic activities and adapt to the current era of information technology. The most dominant micro businesses in Pancoran Mas District are businesses engaged in the culinary sector. One effort to increase the marketing reach of micro-businesses in Pancoran Mas District, especially in the culinary sector, is by utilizing e-commerce. This study was conducted to determine the differences between income, product sales, and marketing reach before and after the utilization of e-commerce. The method used in this study is the quantitative descriptive method. The results of the study indicate that from the processing of the wilcoxon test, there is a significant difference between income, product sales, and marketing reach before and after the use of e-commerce by culinary micro-businesses actors in Pancoran Mas District, Depok City.